Correlation of Serum Bilirubin with Severity of Acute Ischemic Stroke: Serum Bilirubin with Severity of Acute Ischemic Stroke - Awan, Muhammad Naeem; Kanwal, Sibgha; Moinuddin, Imran Ahmed; Ashfaq, Aniqa; Sadia, Anam; Munir, Fariha; Waseem, Humaira (Pakistan Journal of Health Sciences, 2025)
Serum bilirubin is associated with stroke severity, existing data on this relationship remain limited and inconclusive. Objectives: To determine the correlation between serum bilirubin and the National Institute of Health stroke scale score in patients with acute ischemic stroke. Methods: This cross-sectional study was done at the Medical Emergency of Mayo Hospital Lahore from June 2022 to December 2022. A total of 205 patients suffering from acute ischemic stroke were included. Serum bilirubin was obtained within 24 hours of the onset of stroke at presentation, and stroke severity was assessed same time using NIHSS. Data analysis was done using SPSS version 26.0. Pearson correlation was determined between serum bilirubin and NIHSS score at presentation. Results: In current study population, 44.5% of patients were diabetics, 77.6% were hypertensive, and 27.8% were smokers. Mean serum bilirubin level was 0.98 ± 0.19 mg/dL, and mean NIHSS score is 19.51 ± 8.94, Pearson correlation coefficient between bilirubin and NIHSS is -0.082, p-value=0.240, statistically not significant. Conclusions: It was concluded that in our study, a weak negative correlation was observed between serum bilirubin levels and NIHSS scores in patients with acute ischemic stroke. This suggests that higher bilirubin levels may have a slight protective effect, as stroke severity (NIHSS scores) tended to decrease minimally with increasing bilirubin levels.